PENGARUH PENGHARGAAN, BUDAYA ORGANISASI DAN STRUKTUR ORGANISASI TERHADAP EFEKTIVITAS ORGANISASI PADA PT. PERUSAHAAN LISTRIK NEGARA AREA PEKANBARU - Vernando, Irvan; Rifqi, Ahmad; ', Nuryanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research held in PLN Pekanbaru Area. This research held in order to analyze the effect of reward, organizational culture and organizational structure to organizational effectiveness. Population are all employees, consist of 62 people. Considering the number limitation so sampling method used is census that covers all employee as the respondents.Variables used are reward, organizational culture and organizational structure as independent and organizational effectiveness as dependent. Data analyzed by using descriptive analysis and multiple regression analysis by using SPSS 19 for windows.Result of this study shows that reward, organizational culture and organizational structure significantly effect on organizational effectiveness. Partially, reward and organizational structure shows positive and significant effect on organizational effectiveness, while organizational culture gives no significant effect.It is recommended to company to adjust the normative incentives with the inflation growth and provide additional tools for each division. The culture of effective and efficient process and enhance the public service motivation and accountability need to be overcome. It is also recommended to place the right man in the position and expand the human resource division.Keywords: Reward, Organizational Culture, Structure, and Effectiveness